2010
DOI: 10.1016/j.jvs.2010.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Complications With Dual Antiplatelet Therapy Among Patients With Stable Vascular Disease or Risk Factors for Vascular Disease: Results From the Clopidogrel for High Atherothrombotic Risk and Ischemic Stabilization, Management and Avoidance (CHARISMA) Trial

Abstract: Conclusion:High-density lipoprotein is the most important lipid in predicting the risk of development of an abdominal aortic aneurysm (AAA).Summary: The relationship between dyslipidemia and development of AAA is unclear. Some studies have reported an association between lowdensity lipoprotein (LDL) or high-density lipoprotein (HDL) and AAA; others have found no association. Previous studies have not used consistent definitions of dyslipidemia, have not stratified the current use of lipid modifying medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 0 publications
1
82
1
6
Order By: Relevance
“…In the CURE trial, GI bleeding occurred in 1.3% of patients over a 3-to 12-month period [5]. Berger et al [21] recently reported the bleeding complications associated with dual antiplatelet therapy in the CHARISMA trial, which compared aspirin with dual antiplatelet therapy in patients with stable vascular disease or risk factors for vascular disease. In this trial, the addition of clopidogrel led to a 48% relative increase in the risk of moderate or severe bleeding.…”
Section: Clopidogrel Therapy and Gi Bleedingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CURE trial, GI bleeding occurred in 1.3% of patients over a 3-to 12-month period [5]. Berger et al [21] recently reported the bleeding complications associated with dual antiplatelet therapy in the CHARISMA trial, which compared aspirin with dual antiplatelet therapy in patients with stable vascular disease or risk factors for vascular disease. In this trial, the addition of clopidogrel led to a 48% relative increase in the risk of moderate or severe bleeding.…”
Section: Clopidogrel Therapy and Gi Bleedingmentioning
confidence: 99%
“…Fifty-three percent of these bleeding events were GI-related, with an overall rate of 1.7% at 28 months. After multivariate analysis, GI bleeding was associated with allcause mortality with an adjusted hazard ratio (HR) of 1.82 (95% CI, 1.24-2.69) [21].…”
Section: Clopidogrel Therapy and Gi Bleedingmentioning
confidence: 99%
“…Clopidogrel use was associated with a more than doubled bleeding risk in patients older than 75 years [48]. Also the use of glycoprotein IIb/IIIa inhibitors was linked with bleeding risk in octogenarians [49].…”
Section: Risk Assessment Tools and Considerations For Revascularizatimentioning
confidence: 99%
“…In a 28-month trial of clopidogrel, 3.1% of the 15,603 patients had severe or moderate bleeding complications, most commonly gastrointestinal bleeding. Bleeding was increased by older age, heart failure, diabetes, and the use of clopidogrel (55). The occurrence of either bleeding, MI, or stroke each increased the risk for death during follow-up by more than 2-fold (55).…”
Section: Safety Of Carementioning
confidence: 99%